PENGELOLAAN KEUANGAN OLEH PENGUSAHA PEREMPUAN PADA BEBERAPA BISNIS KREATIF DI BANDUNG (Studi Kasus Pada Bisnis Kreatif : fesyen, kerajinan, dan film) - Inge Barlian; Budiana Gomulia; Elvy Maria Manurung (Research Report - Humanities and Social Science, 2012)
Purpose-This paper presents interviews with several women entrepreneur in Bandung who dedicate herself in creative businesses. These creative businesses give challenges to woman today to take a part, as an entrepreneur beside a woman.Design/methodology/approach – The research use qualitative methods with discource analysis with following step : observation, deep interviews and focus group discussion.Findings – The interviews describe that challenged by the economy doesn’t make women entrepreneur in Bandung stop to create. There are five women who have interviewed, and all of them have passionate, always come with new and bright ideas. All of them got supported by their family. With inadequate financial literacy (management) and improper accounting, they still could manage the mixed sources of fund to great succeed, but they have to fix the problem in the future.Originality/value – This paper gives insights that todays women in Bandung are more empowered and stand equally with their men counterpart.Keywords : women entrepreneur, creative business, financial management.